Identification and Functional Validation of Autolysis—Associated Genes in Lactobacillus bulgaricus ATCC BAA-365 - Pang, Xiaoyang; Zhang, Shuwen; Lu, Jing; Liu, Lu; Ma, Changlu; Yang, Yang; Ti, Panpan; Gao, Weihua; Lv, Jiaping (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) are important organisms in food production. Indeed, LAB autolysis is very critical in dairy processing. For example, it influences the development of cheese flavor by releasing intracellular enzymes, and controls cell growth in yogurts and probiotic products. Two component systems (TCS) constitute essential environmental sensors and effectors of signal transduction in most bacteria. In the present work, mutants of one TCS (LBUL_RS00115/LBUL_RS00110) were generated to assess the relationship between TCS and cell autolysis. The mutants displayed decreased autolysis in comparison with wild type; meanwhile, complementation reversed this effect. The interaction between LBUL_RS00115 and LBUL_RS00110 was confirmed by yeast two-hybrid analysis. These observations suggested that the TCS (LBUL_RS00115/LBUL_RS00110) was involved in autolysis in Lactobacillus delbrueckii subsp. bulgaricus.